When indexicals target discursively subsidiary information: How foregrounding and backgrounding in discourse affect indexical reference - Francis Cornish (Discours)
Adopting Berrendonner’s (1990; fc.) distinction between “micro-syntax” and “macro-syntax”, as well as the orthogonal one between foregrounded and backgrounded discourse segments (cf. Khalil, 2005), this paper aims to examine certain “non-canonical” interactions amongst these domains. In particular, I shall be looking at instances where a potential referent is evoked within a highly presupposed, discursively backgrounded text segment, but where that referent is targeted either via an “anadeictically”-used or a non-anaphorically used indexical expression and made into a discourse entity in its own right. The latter is characteristic of discourse deixis, but not of anaphora as such. I will also be looking at larger stretches of text, which relate to each other discursively in terms of “macro-syntax”. I will try to characterise the limits of discourse-anaphoric reference as a function of the degree of backgrounding or foregrounding of the discourse units in terms of which that referent is determined and targeted.